2011
DOI: 10.1159/000324811
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hyperbaric Oxygenation on Postradiation Xerostomia and Saliva in Patients with Head and Neck Tumours

Abstract: The study was designed to evaluate the influence of hyperbaric oxygenation (HBO) therapy on salivary gland function and the growth of salivary Streptococcus mutans,Lactobacillus and Candida albicans in patients with head and neck tumours who had undergone radiation therapy. Sixteen patients were included, with radiation doses from 58 to 70 Gy. The first examination was performed at baseline before the first HBO therapy (33.7 ± 9 months after radiation therapy), and the second after 20 daily HBO therapies in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…Subjective and objective aspects of salivary function are improved with those technique. 189,190 In addition to this, hyperbaric oxygen in irradiated patients demonstrates increased salivary function 191 and reduction in the number of cariogenic bacteria and Candida albicans. Teguh et al 192 pointed out that hyperbaric oxygen favours neoangiogenesis and recruitment of bone marrow stem cells.…”
Section: Topical and Systemic Stimulantsmentioning
confidence: 98%
“…Subjective and objective aspects of salivary function are improved with those technique. 189,190 In addition to this, hyperbaric oxygen in irradiated patients demonstrates increased salivary function 191 and reduction in the number of cariogenic bacteria and Candida albicans. Teguh et al 192 pointed out that hyperbaric oxygen favours neoangiogenesis and recruitment of bone marrow stem cells.…”
Section: Topical and Systemic Stimulantsmentioning
confidence: 98%
“…Overall, both studies found that HBOT increases stimulated salivary flow rates, implying that HBOT may improve xerostomia. 8,11 Visual analog scale Forner et al also used a 10-mm VAS to assess subjective changes in xerostomia after HBOT. 11 Through this study, he found that all patients had a significant improvement in xerostomia, as determined by their VAS score.…”
Section: Salivary Flow Ratesmentioning
confidence: 99%
“…Affected patients have decreased salivary flow rates and viscous saliva that has less bicarbonate, lysozyme, and immunoglobulins. 4,[7][8][9] This change in the character of the saliva contributes to the sensation of dry mouth; difficulty eating, speaking, and swallowing; and a decline in overall quality of life (QoL). Additionally, the physical changes in saliva create an oral environment prone to infections and dental decay.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As oxygen under pressure is dissolved in plasma, it can reach otherwise hypoxic areas with obstructed blood flow, like radiation-injured tissues. In the case of the prevention or treatment of xerostomia, some clinical trials report positive effects of HBOT (6)(7)(8), mostly measured by quality of life questionnaires. Experimental evidence on the beneficial effects of HBOT on irradiated salivary glands is however scarce (9).…”
Section: Introductionmentioning
confidence: 99%